2020
DOI: 10.2196/16887
|View full text |Cite
|
Sign up to set email alerts
|

Using Blockchain Technology to Mitigate Challenges in Service Access for the Homeless and Data Exchange Between Providers: Qualitative Study

Abstract: Background In the homeless population, barriers to housing and supportive services include a lack of control or access to data. Disparate data formats and storage across multiple organizations hinder up-to-date intersystem access to records and a unified view of an individual’s health and documentation history. The utility of blockchain to solve interoperability in health care is supported in recent literature, but the technology has yet to be tested in real-life conditions encompassing the complex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Our prior study based on qualitative interviews with PEH in Austin, Texas, showed that at least one third of clients lacked a basic identity document when they entered the health and human services system in the city. 11 A survey of homeless service providers conducted by the National Law Center on Homelessness and Poverty revealed that the lack of a photo ID prevented PEH from receiving food stamps, social security income (SSI) benefits, Medicaid, shelter or housing services, or medical services; furthermore, ever since September 11, 2001, federal and state laws and administrative policies have made it more difficult for PEH to obtain a photo ID. 12 Second, health care and social services in the U.S. are fragmented and siloed, and in the absence of a truly person-centered and integrated approach, health care and social service systems lack interoperability and are unable to accurately collect, share, and verify even basic identity information for a person experiencing homelessness.…”
Section: Nameless Facesmentioning
confidence: 99%
See 4 more Smart Citations
“…Our prior study based on qualitative interviews with PEH in Austin, Texas, showed that at least one third of clients lacked a basic identity document when they entered the health and human services system in the city. 11 A survey of homeless service providers conducted by the National Law Center on Homelessness and Poverty revealed that the lack of a photo ID prevented PEH from receiving food stamps, social security income (SSI) benefits, Medicaid, shelter or housing services, or medical services; furthermore, ever since September 11, 2001, federal and state laws and administrative policies have made it more difficult for PEH to obtain a photo ID. 12 Second, health care and social services in the U.S. are fragmented and siloed, and in the absence of a truly person-centered and integrated approach, health care and social service systems lack interoperability and are unable to accurately collect, share, and verify even basic identity information for a person experiencing homelessness.…”
Section: Nameless Facesmentioning
confidence: 99%
“…Blockchain technology can be used to ensure secure and portable identity management in health care, and holds great promise to be a techQuity solution for the problem of identity management for PEH. 11,14 Fundamentally, blockchain can be described as a distributed trust network that uses cryptography or encryption to share ledgers of transactions across a large number of nodes. 16 Each piece of information must be verified by a consensus mechanism where all participants of the network agree on the truth of each transaction.…”
Section: A Potential Techquity Solutionmentioning
confidence: 99%
See 3 more Smart Citations